'Why I Sent My Child Away': Culturally Structured Motivations for Long-distance Parenting. (March 2017) - Srivastava, Deepa; de Guzman, Maria Rosario T.
Although long-distance parenting is often depicted as a response to crisis (e.g., economic) or other stressful life events, it is sometimes undertaken in various culturally normative situations. This current study explores the motivations of South Asian Indian immigrant parents for sending their young children to India to live temporarily with their grandparents. This qualitative study involves in-depth interviews with first generation immigrant parents about their experiences and motivations for sending their children to India. Analysis of the data revealed five themes, namely, (a) contextual and daily challenges in caring for their children in the United States, (b) parents' concern around paid group childcare, (c) grandparents as ideal caregivers but unable to stay in the United States, (d) presence of other extended network of relationships and support in India and (e) parents wanting their children to maintain their language and customs. Findings suggest culturally grounded beliefs around optimal childrearing (e.g., grandparents as ideal caregivers, presence of extended network of support in India and maintaining Indian traditions and values) and parents' contextual needs (e.g., parents' busy schedule around job and education) when traditional caregiving context changes due to migration to a new country. Implications for researchers are discussed.